Lost. The complete second season. The extended experience [videorecording (DVD)] - Akinnuoye-Agbaje, Adewale, 1967-; Andrews, Naveen, 1969-; De Ravin, Emilie, 1981-; Fox, Matthew, 1966-; Garcia, Jorge, 1973- (Distributed by Buena Vista Home Entertainment, 2006)
While Jack, Kate, and Locke investigate what's inside the hatch, the "tailies" are found. These survivors are from the tail of the plane and include tough girl Ana-Lucia and the spiritual and mysterious Mr. Eko. Learn what happened to Walt when he left Michael with some very hard choices to make and get a better insight into just who the "others" are. Find out that the island has some connection with the Dharma Corporation.